Pengaruh Cita Rasa dan Word Of Mouth terhadap Keputusan Pembelian pada Rumah Makan Dieng Prabumulih (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the partial and simultaneous effects of taste and word of mouth on purchasing decisions at Rumah Makan Dieng Prabumulih. The sample consisted of 100 respondents who are customers of Rumah Makan Dieng Prabumulih. This research employed a quantitative method with a descriptive approach using questionnaires as the primary data collection tool. The data were analyzed using multiple linear regression with SPSS version 26. The statistical test results indicate that the taste variable has a positive and significant partial effect on purchasing decisions, with a t-value of 4.265 greater than the t-table value of 1.661 and a significance level of 0.000 < 0.05. Similarly, the word of mouth variable has a positive and significant partial effect on purchasing decisions, with a t-value of 4.455 > 1.661 and a significance level of 0.000 < 0.05. Simultaneously, the taste and word of mouth variables have a positive and significant effect on purchasing decisions, with an F-value of 56.467 > 3.09 and a significance level of 0.000 < 0.05. The coefficient of determination (Adjusted R Square) is 0.528, indicating that 52.8% of purchasing decisions are influenced by taste and word of mouth, while the remaining 47.2% are influenced by other factors such as price, location, and so on.